The relationship between obesity and quality of life in Brazilian adults - Pimenta, Fernanda B. C.; Bertrand, Elodie; Mograbi, Daniel C.; Shinohara, Helene; Landeira-Fernandez, J. (Frontiers in Psychology, 2015)
The incidence of obesity has reached epidemic proportions, affecting 30% of the adult population globally. During the last decade, the rising rates of obesity in developing countries has been particularly striking. One potential consequence of obesity is a decline in quality of life. Thus, the objective of the present study was to investigate the possible relationship between obesity, defined by body mass index (BMI), and quality of life, evaluated using the short version of the World Health Organization Quality of Life (WHOQOL) scale in a Brazilian population. The sample consisted of 30 men and 30 women, divided into three groups according to BMI: normal weight, obese, and morbidly obese. All of the subjects responded to the WHOQOL inventories. The results indicated that the groups with lower BMIs had better quality of life than the groups with higher BMIs. Being overweight interfered with quality of life equally in both sexes, with no difference found between men and women. The results indicate the necessity of multidisciplinary care of obese individuals.